Changing demographic pattern of Dausa District: दौसा जिले का बदलता जनांकिकीय स्वरूप - Doriya, Rakesh (RESEARCH HUB International Multidisciplinary Research Journal, 2023)
In the context of resource allocation in geographic perspective, the profound importance of human resource populations emerges. Its significance lies in the dynamic interplay between the economic progress of a particular location and the existing human capital. Human agents, using their ability to effectively exploit natural resources, form a critical link that links resource use and human agency, all of which are based on human skill. It is worth underlining that natural resources have an inherently passive quality, which acts as a catalyst for economic growth. This is in stark contrast with the human drive, which aims to optimize the productivity derived from these basic resources. As a result, the judicious exploitation of natural resources and the imminent course of industrial and commercial development within a specific area depends on the local distribution and demographic concentration of the resident population, as well as on the inherent characteristics and functional competencies of its constituents. This complex interplay underlines the imperative of a thorough investigation of human resource structure within an immediate region in different chronological periods. Abstract in Hindi Language: भौगोलिक संदर्भों में संसाधनों के आवंटन के संदर्भ में, मानव संसाधन आबादी का गहरा महत्व उभर कर आता है। यह महत्व किसी विशेष स्थान की आर्थिक प्रगति और मौजूदा मानव पूंजी के बीच गतिशील परस्पर क्रिया में निहित है। मानव एजेंट, प्राकृतिक संसाधनों का प्रभावी ढंग से दोहन करने की अपनी क्षमता का उपयोग करते हुए, एक महत्वपूर्ण कड़ी बनाते हैं जो संसाधन उपयोग और मानव एजेंसी को जोड़ती है, जो सभी मानव कौशल पर आधारित हैं। यह रेखांकित करने योग्य है कि प्राकृतिक संसाधनों में स्वाभाविक रूप से एक निष्क्रिय गुण होता है, जो आर्थिक उन्नति के लिए उत्प्रेरक के रूप में कार्य करता है। यह मानव ड्राइव के साथ बिल्कुल विपरीत है, जिसका उद्देश्य इन मूल संसाधनों से प्राप्त उत्पादकता को अनुकूलित करना है। परिणामस्वरूप, प्राकृतिक संसाधनों का विवेकपूर्ण दोहन और एक विशिष्ट क्षेत्र के भीतर औद्योगिक और वाणिज्यिक विकास का आसन्न पाठ्यक्रम निवासी आबादी के स्थानीय वितरण और जनसांख्यिकीय एकाग्रता के साथ-साथ इसके घटकों की अंतर्निहित विशेषताओं और कार्यात्मक दक्षताओं पर निर्भर करता है। यह जटिल परस्पर क्रिया विभिन्न कालानुक्रमिक अवधियों में एक तत्काल क्षेत्र के भीतर मानव संसाधन संरचना की गहन जांच की अनिवार्यता को रेखांकित करती है। Keywords: जनसांख्यिकीय, प्राकृतिक संसाधन, औद्योगिक, वाणिज्यिक विकास